2019
DOI: 10.1186/s12957-019-1710-9
|View full text |Cite
|
Sign up to set email alerts
|

Selective occlusion of the hepatic artery and portal vein improves liver hypertrophy for staged hepatectomy

Abstract: Background To evaluate the safety and feasibility of selective occlusion of the hepatic artery and portal vein (SOAP) for staged hepatectomy (SOAPS) in patients with hepatocellular carcinoma (HCC) Methods From December 2014 to August 2018, 9 patients with unresectable HCC were chosen to undergo SOAPS. SOAP without liver partition was performed in the first stage. The second stage was performed when future liver remnant (FLR) was equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Advances in systemic chemotherapy have allowed for more patients with extensive CLRM to undergo liver resection through down-sizing chemotherapy strategies. Moreover, staged procedures with FLR augmentation through PVE have further increased resectablity rates [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. In this study, we specifically evaluated the concept of TSH with PVE after CU of the left liver lobe.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in systemic chemotherapy have allowed for more patients with extensive CLRM to undergo liver resection through down-sizing chemotherapy strategies. Moreover, staged procedures with FLR augmentation through PVE have further increased resectablity rates [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. In this study, we specifically evaluated the concept of TSH with PVE after CU of the left liver lobe.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive surgical and occlusion times have been associated with increased instances of liver failure and mortality. These conditions facilitate hypothermia or ischemia-reperfusion injury, which stimulates Kupffer cells to produce oxygen-free radicals, initiating inflammatory responses that ultimately lead to endothelial damage and impairments in coagulation mechanisms[ 20 ]. These findings underscore the necessity for assertive anticoagulation therapy following hepatic operations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inhibiting tumor angiogenesis can inhibit tumor cell growth and metastasis. Previous studies [ 41 , 52 ] has shown that tumor angiogenesis is a dynamic process with multi-factors participation. The signal cascade mediated by VEGFR-2 is the key regulatory pathway, which can regulate the proliferation, migration, survival and permeability of vascular endothelial cells [ 53 ].…”
Section: Discussionmentioning
confidence: 99%